2015
DOI: 10.1007/s10071-015-0888-7
|View full text |Cite
|
Sign up to set email alerts
|

Titmouse calling and foraging are affected by head and body orientation of cat predator models and possible experience with real cats

Abstract: Although anti-predator behavior systems have been studied in diverse taxa, less is known about how prey species detect and assess the immediate threat posed by a predator based on its behavior. In this study, we evaluated a potential cue that some species may utilize when assessing predation threat-the predator's body and head orientation. We tested the effect of this orientation cue on signaling and predation-risk-sensitive foraging of a prey species, tufted titmice (Baeolophus bicolor). Earlier work revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 50 publications
1
39
0
Order By: Relevance
“…Seed‐taking rates of tufted titmice and white‐breasted nuthatches did not appear to be associated with owl stimulus intensity or with background noise. Seed‐taking rates in these species tended to decrease in the context of threatening or risky stimuli in previous studies that presented visual predator stimuli to prey birds (Bartmess‐LeVasseur et al, ; Book & Freeberg, ; Cantwell, Johnson, Kaschel, Love, & Freeberg, ; Freeberg, Krama, Vrublevska, Krams, & Kullberg, ; Kyle & Freeberg, ). Perhaps foraging behavior in these species is more sensitive to predator stimuli in the visual, rather than the acoustic, domain.…”
Section: Discussionmentioning
confidence: 65%
“…Seed‐taking rates of tufted titmice and white‐breasted nuthatches did not appear to be associated with owl stimulus intensity or with background noise. Seed‐taking rates in these species tended to decrease in the context of threatening or risky stimuli in previous studies that presented visual predator stimuli to prey birds (Bartmess‐LeVasseur et al, ; Book & Freeberg, ; Cantwell, Johnson, Kaschel, Love, & Freeberg, ; Freeberg, Krama, Vrublevska, Krams, & Kullberg, ; Kyle & Freeberg, ). Perhaps foraging behavior in these species is more sensitive to predator stimuli in the visual, rather than the acoustic, domain.…”
Section: Discussionmentioning
confidence: 65%
“…Regardless of the meaning coded in the call variation, the results demonstrate a graded system of signaling based on the duration, rate, proportion, and center frequency of “LF/churr/rattle/jar” notes in the vocal response of the oriental tit. This is reminiscent of signaling observed in parids from genus Beolophus and Poecile where the higher level of threat by a predator is coded in the higher number of D notes in their vocal response to predators (Book & Freeberg, ; Courter & Ritchison, ; Sieving, Hetrick, & Avery, ; Soard & Ritchison, ; Templeton et al, ). The suggested role of the number of “LF/churr/rattle/jar” notes in coding information about predators by the oriental tit can be extracted from the results reported by Suzuki (Suzuki, ).…”
Section: Discussionmentioning
confidence: 89%
“…This kind of alarm system can help prey animals to share information about predators and to recruit prey individuals into a mobbing group (Hurd, ; Lima & Dill, ; Peres, ; Cooper & Blumstein, ). Similar alarm communication systems exist in birds (e.g., Carlson, Templeton, & Healy , ; Ficken & Popp, ; Gill & Bierema, ; Suzuki, , ) where various characteristics of the alarm vocalizations may carry information about predator type (Fasanella & Fernández, ; Griesser, ; Naguib et al, ; Yorzinski & Vehrencamp, ), predator size (Templeton, Greene, & Davis, ), degree of threat (Soard & Ritchinson, ; Carlson et al, ), predator behavior (Griesser, ), or a predator's facial orientation (Book & Freeberg, ; Freeberg, Krama, Vrublevska, Krams, & Kullberg, ). The information about the predator may be coded in the use of different types of calls/notes and in the number/proportion of notes of each type as well as in detailed temporal and frequency characteristics of the notes (Templeton et al, ; Carlson et al, ).…”
Section: Introductionmentioning
confidence: 90%
“…Recent work with tufted titmice, Baeolophus bicolor , indicated that birds reduced foraging when a mask‐wearing human (Freeberg et al. ) or a cat model (Book & Freeberg ) faced the feeding station the birds were using, compared to when the potential predator was not facing the feeding station. Furthermore, titmice called more when the mask‐wearing human faced toward, rather than away from, the feeding station (Freeberg et al.…”
Section: Introductionmentioning
confidence: 99%